Carbon dots in photodynamic therapy - Matin, Mahdie; Mirhoseinian, Mahtab; Alikhanian, Alireza; Bayatani, Golnar; Montazer, Mohammad Nazari; Mahdavic, Mohammad; Tüzün, Burak (De Gruyter, 2023)
Carbon dots (CDs) as a subclass of carbon-based nanoparticles were first discovered in 2004 and attracted the attention of scientists worldwide to their extinguish physiochemical properties; nowadays CDs have a broad range of applications including bioimaging, photocatalysis, fluorescent ink, sensors, lasers, and LED. In this chapter we will have a look into the synthesis, structure, and applications of CDs on biomedical science such as bioimaging, biosensors, drug and gene delivery, and photodynamic therapy. Photodynamic therapy is the method to transfer light energy to its surrounding using photosensitizer structure trials, which showed meaningful response to this approach in many types of malignancies, CDs could be a suitable option to use as photosensitizers. © 2023 Elsevier B.V., All rights reserved.
Keywords: Biomedical Sciences; Cancer; Carbon Dots; Nanoparticles; Photodynamic Therapy